DAMPAK KREDIT PROGRAM KKPE DALAM PENGEMBANGAN USAHA TERNAK SAPI DI TINGKAT PETERNAK DI JAWA TENGAH - Dahri Dahri; Parulian Hutagaol; Hermanto Siregar; Pantjar Simatupang (School of Business, Bogor Agricultural University (SB-IPB), 2015)
The impact of energy and food security credits (KKPE) to the cattle farming performance at the farm level is importan tto be studied related to improving the welfare of the cattle farmers and also the achievement of self-sufficiency in food, especially meat self-sufficiency. The number of KKPE distributed since 2007, continued to increase from year to year, but the performance of the livestock subsector is not yet fully accordance with the expectations. Therefore, the objective of this study is to analyze the impact of KKPE to the number of cattle owned by the farmer, employment and income of the cattle farming. The main data used are primary data collected through interviews using a questionnaire to124 cattle farmers recipient and non recipientKKPE in Central Java and determined using purposive sampling method. Results ofthe study usingLinear regression models of the ordinary least squares (OLS) approach indicates that KKPE provide a positive influence on the number of cattle owned by farmers, employment and income of the cattle farming where the influence of the KKPE are all significant except for the impact on business income of cattle. Thus, in order to encourage the improvement of the welfare of farmers and the achievement of self-sufficiency in meat, KKPE needs to be developed with the control the credit delivery system is able to provide incentives for farmers to continue to expand its cattle farming.Keywords: Cattle farmer, impact of the KKPE, KKPE Credit program, OLSABSTRAKDampak kredit ketahanan pangan dan energi (KKPE) terhadap kinerja usaha sapi di tingkat peternak merupakan hal yang penting untuk dikaji terkait dengan upaya peningkatan kesejahateraan peternak dan juga pencapaian swasembada pangan, khususnya swasembada daging. Nilai KKPE yang disalurkan sejak tahun 2007, terus mengalami peningkatan dari tahun ke tahun, namun kinerja subsektor peternakan belum sepenuhnya sesuai dengan harapan. Oleh karena itu, tujuan penelitian ini adalah menganalisis dampak KKPE terhadap jumlah sapi yang dipelihara, penyerapan tenaga kerja serta pendapatan usaha sapi peternak. Data utama yang digunakan berupa data primer yang dikumpulkan melalui wawancara dengan menggunakan kuesioner pada 124 peternak sapi penerima dan non penerima KKPE di Jawa Tengah dimana sampel peternak tersebut ditentukan dengan menggunakan metode purposive sampling. Hasil studi dengan menggunakan Model Regresi Linier Sederhana (Linear regression models of the ordinary least square (OLS) approach) menunjukkan bahwa KKPE memberikan pengaruh yang positif terhadap jumlah sapi yang dimiliki peternak, penyerapan tenaga kerja. Pengaruh tersebut semuanya signifikan, kecuali untuk dampaknya terhadap pendapatan usaha sapi. Dengan demikian, untuk dapat mendorong peningkatan kesejahteraan peternak dan pencapaian swasembada daging, KKPE perlu terus dikembangkan dengan pengendalian pada sistem penyaluran kredit yang mampu memberikan insentif bagi peternak untuk terus mengembangkan usahanya.Kata kunci: Kredit program KKPE, dampak KKPE, peternak sapi, OLS